FARM ENTREPRENEURSHIP AS A KEY FACTOR IN REGIONAL DEVELOPMENT: WAYS TO ACHIEVE STRATEGIC PRIORITIES - RUDACHENKO, OLHA; KONDRATENKO, NATALIIA (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article discusses the role of farms as an essential sector of Ukraine's economy in the context of socio-economic transformations and European integration. The author emphasizes the importance of farming for developing agriculture, creating jobs in territorial communities and improving living standards. The dynamics of the farm sector development, its contribution to agricultural production, peculiarities of land resources distribution and regional differences in farming development are investigated. The necessity of support and development of farms as a factor of regional development, economic stability and improvement of the social status of the rural population is substantiated.At the same time, the article notes that the development of farms in different regions of Ukraine is not the same, which is due to natural and climatic conditions and other regional features. Farms are a powerful factor ensuring the growth of agricultural production, efficient use of natural resource potential and strengthening the socio-economic structure of territorial communities. Their activities contribute to increasing employment, filling local budgets and providing the population with the necessary products. The paper also classifies farms by specialization, legal status, and size, allowing for a better understanding of various forms. The essence of farm entrepreneurship is defined as a separate form of management based on the use of land plots for the production of agricultural products for sale on the market and profit. The article emphasizes the strategic importance of farm entrepreneurship for increasing employment, strengthening local budgets and developing territorial communities. The author identifies key areas of strategic development of the industry, including improvement of lending, introduction of innovative technologies, expansion of training and consulting support, development of cooperation between producers and formation of a favorable legislative environment. The author emphasizes the need to develop practical mechanisms for implementing these priorities, taking into account sectoral and regional specifics, to ensure the sustainable development of farms and strengthen the economy of Ukraine.
Keywords: farm entrepreneurship; farming; regional development; region; territorial communities; strategic management; priority; agricultural enterprise